Method for detecting total content of lanthanum element and cerium element in vanadium titano-magnetite
By using acid solution dissolution and perchloric acid smoke in acidic media, a blue complex of lanthanum and cerium elements was formed, and their absorbance was measured by photometric method, the problem of incomplete matrix effect and determination in the prior art was solved, and a rapid and accurate quantitative analysis of the total content of lanthanum and cerium elements in vanadium titanium magnetite was achieved.
Patent Information
- Application Number
- CN202411656613.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, when detecting the total content of lanthanum and cerium in vanadium titanium magnetite, there is a risk of matrix effects and incomplete measurement and low results.
Using acid solution and perchloric acid smoke, in acidic media with pH 0.2~3.0, lanthanum, cerium elements and azochlorodurophosphine mA form a blue complex, their absorbance is determined by photometric method, and the total content of lanthanum and cerium elements is calculated according to the standard curve.
It realizes rapid and accurate quantification analysis of the total content of lanthanum and cerium, and has the advantages of high sensitivity, good stability, accurate quantification, short detection time and low cost.
Smart Images

Figure SMS_4 
Figure FDA0005142249440000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials and metallurgy, and more specifically, to a method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite. Background Art
[0002] Vanadium-titanium magnetite is an iron ore with special element content. Its chemical composition content and sample dissolution method are unique. Cerium (Ce) and lanthanum (La) are the main rare earth elements in vanadium-titanium magnetite. The change in the content of Ce and La rare earth elements has a certain influence on the chemical properties of vanadium-titanium magnetite. Among them, rare earth cerium can play the role of metamorphic inclusions, purifying molten steel, and micro-alloying in steel. Rare earth lanthanum is a deoxidizer and alloying element of steel in the steel production process. It can effectively reduce the brittleness of steel and improve the hardness, toughness and heat resistance of steel. In addition, the addition of can also improve the cold processing performance of steel and improve the quality of steel. Therefore, it is very important to accurately determine Ce and La in vanadium-titanium magnetite.
[0003] A Chinese patent with application number 202110007351.5 discloses a method for determining the content of lanthanum, cerium, praseodymium, neodymium, samarium, calcium, and magnesium in iron ore. The method uses sodium hydroxide-sodium peroxide to melt and decompose the sample, leaching with water, acidifying with hydrochloric acid, and separating calcium and magnesium elements with ammonia water. The filtrate after filtration is fixed to volume, and the calcium and magnesium content is determined by ICP-AES; the filtered precipitate is dissolved with hydrochloric acid and fixed to volume, and then the lanthanum, cerium, praseodymium, neodymium, and samarium content is determined by ICP-AES. However, it uses an alkaline flux, introduces a large amount of sodium ions, increases the matrix effect, and uses filtration and precipitation to separate the elements to be measured, which also has the risk of incomplete determination and low results. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and provide a method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite with high sensitivity, good stability, accurate quantification, short detection time and low cost.
[0005] To achieve the above object, the technical solution of the present invention is as follows: A method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite comprises the following steps: (1) After the sample is dissolved in acid solution, add perchloric acid, heat and evaporate until white perchloric acid smoke appears, rinse the container wall with water, continue to heat and evaporate until white perchloric acid smoke appears to the cup mouth, cool it down, dissolve the salt in water, and make up to volume with water to obtain the sample solution to be tested; prepare the blank solution in the same way; (2) preparing a gadolinium standard solution: selecting a high-purity gadolinium oxide standard product, dissolving it in hydrochloric acid, and preparing a gadolinium stock solution; measuring the gadolinium stock solution, adding the blank solution prepared in step (1) to dilute it, and preparing a gadolinium standard solution with a gradient concentration; (3) Prepare the colorimetric solution and reference solution: Add oxalic acid and chlorophosphonazo mA to the test sample solution in sequence, and dilute to volume with water to obtain a color developing solution; Add chlorophosphonazo mA to the blank solution to make a reference solution; At the same time, prepare the colorimetric solution and reference solution of the gadolinium standard solution respectively in the same manner; (4) Using a spectrophotometer to measure the absorbance of the colorimetric solution and the reference solution of the gadolinium standard solution to obtain a standard curve, wherein the abscissa of the standard curve is the total content of lanthanum and cerium, and the ordinate is the absorbance; and under the same conditions, the absorbance of the colorimetric solution and the reference solution of the test sample solution is measured, and the total content of lanthanum and cerium in the test sample solution is obtained according to the standard curve, and the total content of lanthanum and cerium in the vanadium-titanium magnetite is calculated according to the following formula: w =
[0006] Where: w — Total content of lanthanum and cerium, %; C — The total content of lanthanum and cerium in the test sample solution, μg / mL; C 0 — Blank solution test value, μg / mL; V —Total volume of the sample solution to be tested, mL; m — Mass of the sample, μg.
[0007] Implementing the embodiments of the present invention will have the following beneficial effects: The embodiment of the present invention provides a method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite. First, the sample is dissolved in acid solution, and perchloric acid is used to smoke. In an acidic medium with a pH of 0.2 to 3.0, the lanthanum and cerium combined elements form a blue complex with chlorophosphine azo mA, and the photometric determination is performed. The present invention realizes rapid and accurate quantitative analysis of the total content of lanthanum and cerium. The detection method of the present invention has the advantages of high sensitivity, good stability, accurate quantification, short detection time, low cost, etc. DETAILED DESCRIPTION
[0008] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.
[0009] The invention discloses a method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite, comprising the following steps: (1) After the sample is dissolved in acid solution, add perchloric acid and heat to evaporate until white perchloric acid smoke appears. Rinse the container wall with water and continue to heat and evaporate until white perchloric acid smoke reaches the cup mouth. After cooling, dissolve the salt in water and make up to volume with water to obtain the sample solution to be tested. The blank solution is prepared in the same way.
[0010] (2) Preparation of gadolinium standard solution: Select a high-purity gadolinium oxide standard, dissolve it in hydrochloric acid, and prepare a gadolinium stock solution; measure the gadolinium stock solution, add the blank solution prepared in step (1) to dilute it, and prepare a gadolinium standard solution with a gradient concentration.
[0011] (3) Prepare the colorimetric solution and reference solution: add oxalic acid and chlorophosphonazo mA to the test sample solution in sequence, and make up to volume with water to obtain the colorimetric solution; add chlorophosphonazo mA to the blank solution to make up to volume to obtain the reference solution; at the same time, prepare the colorimetric solution and reference solution of the gadolinium standard solution in the same manner.
[0012] (4) Using a spectrophotometer, the absorbance of the colorimetric solution and the reference solution of the gadolinium standard solution is measured to obtain a standard curve, wherein the abscissa of the standard curve is the total content of lanthanum and cerium, and the ordinate is the absorbance; and under the same conditions, the absorbance of the colorimetric solution and the reference solution of the test sample solution is measured to obtain the total content of lanthanum and cerium in the test sample solution according to the standard curve, and the total content of lanthanum and cerium in the vanadium-titanium magnetite is calculated according to the following formula: w =
[0013] Where: w — Total content of lanthanum and cerium, %; C — The total content of lanthanum and cerium in the test sample solution, μg / mL; C 0 — Blank solution test value, μg / mL; V —Total volume of the sample solution to be tested, mL; m — Mass of the sample, μg.
[0014] In a specific embodiment, step (1) specifically includes the following steps: placing 0.10 g to 3.0 g of a sample in a 150 mL to 300 mL beaker, adding 5 mL to 40 mL of an acid solution to dissolve the sample at 200° C. to 300° C., then adding 4 mL to 20 mL of perchloric acid, heating and evaporating at 210° C. to 400° C. until white perchloric acid smoke is emitted, washing the container wall with water, continuing to heat and evaporate until white perchloric acid smoke is emitted to the cup mouth, cooling and dissolving the salt with water, and then diluting the volume to 50 mL or 100 mL with water.
[0015] In a specific embodiment, the acid solution includes nitric acid (1+3) and / or hydrochloric acid.
[0016] In a specific embodiment, step (1) further comprises: when the mass percentage of Cr in the sample is greater than 1.5%, removing the chromium with hydrochloric acid, and then continuing to heat and evaporate to emit white perchloric acid smoke to the mouth of the cup.
[0017] In a specific embodiment, step (2) specifically includes the following steps: drying high-purity gadolinium oxide at 750° C. to 780° C. for 20 min and cooling to room temperature, weighing 0.1154 g and adding 40 ml of hydrochloric acid (1+1) to dissolve it, cooling it to room temperature, and diluting it to 1000 mL with water to obtain a gadolinium stock solution with a concentration of 100 μg / mL; measuring the gadolinium stock solution, adding a blank solution to dilute it, and preparing gadolinium standard solutions with gadolinium concentrations of 2.0 μg / mL, 10.0 μg / mL, and 100 μg / mL, respectively.
[0018] In a specific embodiment, in step (3), the preparation process of the color developing solution and the reference solution is as follows: take 5.00mL~50.00mL of the sample solution to be tested and add 5ml~20ml of oxalic acid and 5ml~20ml of chlorophosphazo mA in sequence, and dilute with water to obtain the color developing solution; take 5.00mL~50.00mL of the blank solution and add 5ml~20ml of chlorophosphazo mA, and dilute to obtain the reference solution.
[0019] In a specific embodiment, the concentration of oxalic acid is 40 g / L to 250 g / L; the concentration of chlorophosphonazo mA is 0.2 g / L to 4 g / L.
[0020] In a specific embodiment, step (4) specifically includes the following steps: placing the sample color developing solution and the sample reference solution in an absorption dish of 1 cm, 2 cm or 3 cm, taking the reference solution as a reference, measuring the absorbance thereof at 560 nm~760 nm using a spectrophotometer, obtaining the total content of lanthanum and cerium in the test sample solution and the detection value of the blank solution, and calculating the total content of lanthanum and cerium in the vanadium-titanium magnetite.
[0021] In a specific embodiment, the total mass content of lanthanum and cerium in the sample is 0.0001% to 1.0%.
[0022] The following are specific embodiments Example 1 1. Reagents: Unless otherwise specified, only analytical grade reagents and distilled water or water of equivalent purity should be used during analysis.
[0023] 1.1 Nitric acid, about 1.42g / mL1+3; 1.2 Hydrochloric acid, about 1.19g / mL1+1; 1.3 Perchloric acid, about 1.67 g / mL; 1.4 Oxalic acid solution, 50 g / L; 1.5 Chlorophosphonazo mA solution, 0.4 g / L.
[0024] 2. Experimental steps The method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite of this embodiment comprises the following steps: (1) Place 0.2 g of the sample in a 150 mL beaker, add 10 mL of nitric acid (1+3) to dissolve the sample at 250 °C, then add 4 mL of perchloric acid, heat and evaporate at 350 °C until white perchloric acid smoke is emitted, rinse the container wall with water. When the mass percentage of Cr in the sample is >1.5%, use hydrochloric acid to remove chromium, continue to heat and evaporate until white perchloric acid smoke reaches the mouth of the cup, cool and dissolve the salt with water, and then make up to 50 mL with water.
[0025] (2) Preparation of gadolinium standard solution: high-purity gadolinium oxide was dried at 750°C for 20 min and cooled to room temperature. 0.1154 g of the solution was weighed and dissolved in 40 ml of hydrochloric acid (1+1). After cooling to room temperature, the solution was diluted to 1000 mL with water to obtain a gadolinium stock solution with a concentration of 100 μg / mL. The gadolinium stock solution was measured and diluted with blank solution to prepare gadolinium standard solutions with gadolinium concentrations of 2.0 μg / mL, 10.0 μg / mL, and 100 μg / mL, respectively.
[0026] (3) Prepare the colorimetric solution and the reference solution: add oxalic acid and chlorophosphonazo mA to the sample solution to be tested in sequence, and dilute with water to obtain the colorimetric solution; add chlorophosphonazo mA to the blank solution to obtain the reference solution; and prepare the colorimetric solution and the reference solution of the gadolinium standard solution in the same manner. The preparation process of the colorimetric solution and the reference solution is as follows: take 5.00 mL of the sample solution to be tested and add 7 ml of oxalic acid and 5 ml of chlorophosphonazo mA in sequence, and dilute with water to obtain the colorimetric solution; take 5.00 mL of the blank solution and add 5 ml of chlorophosphonazo mA to obtain the reference solution.
[0027] (4) The absorbance of the colorimetric solution and the reference solution of the gadolinium standard solution was measured by a spectrophotometer to obtain a standard curve, wherein the abscissa of the standard curve is the total content of lanthanum and cerium, and the ordinate is the absorbance; and under the same conditions, the sample colorimetric solution and the sample reference solution were placed in a 2 cm absorption dish, and the reference solution was used as a reference. The absorbance was measured at 660 nm by a spectrophotometer to obtain the total content of lanthanum and cerium in the test sample solution and the detection value of the blank solution, and the total content of lanthanum and cerium in the vanadium-titanium magnetite HB2405082 was calculated according to the following formula. The results are shown in Table 1.
[0028] w =
[0029] Where: w— Total content of lanthanum and cerium, %; C — Total content of lanthanum and cerium in the test sample solution, μg / mL; C 0 — Blank solution test value, μg / mL; V —Total volume of the sample solution to be tested, mL; m — Mass of the sample, g.
[0030] Example 2 The difference between this embodiment and embodiment 1 is that 0.5000 g of vanadium-titanium magnetite HB2405071 sample (accurate to 0.0001 g) is weighed, and the detection results of the total contents of lanthanum and cerium in the sample are obtained according to the calculation method of embodiment 1, as shown in Table 1.
[0031] Example 3 The difference between this embodiment and embodiment 1 is that 1.0000 g of vanadium-titanium magnetite HB2405053 sample (accurate to 0.0001 g) is weighed, and the detection results of the total contents of lanthanum and cerium in the sample are obtained according to the calculation method of embodiment 1, as shown in Table 1.
[0032] Table 1 Test results of Examples 1-3
[0033] According to the results in Table 1, the detection methods of Examples 1-3 of the present invention can achieve rapid and accurate quantitative analysis of the total content of lanthanum and cerium, and have the advantages of high sensitivity, good stability, accurate quantification, short detection time, and low cost.
[0034] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite, characterized in that: The following steps are involved: (1) After the sample is dissolved in acid solution, perchloric acid is added, and the solution is heated and evaporated until white perchloric acid smoke is emitted. The container wall is rinsed with water, and the heating and evaporation are continued until white perchloric acid smoke is emitted to the cup mouth. After cooling, the salt is dissolved in water, and the volume is fixed with water to obtain the sample solution to be tested; a blank solution is prepared in the same way; (2) Preparation of gadolinium standard solution: Select high-purity gadolinium oxide standard, dissolve it in hydrochloric acid, and prepare gadolinium stock solution; The gadolinium stock solution is measured and added to the blank solution prepared in step (1) for dilution to prepare a gadolinium standard solution with gradient concentrations; (3) Prepare the color developing solution and reference solution: Add oxalic acid and chlorophosphonazo mA to the test sample solution in sequence, and dilute to volume with water to obtain a color developing solution; Add chlorophosphonazo mA to the blank solution to make a reference solution; At the same time, prepare the colorimetric solution and reference solution of the gadolinium standard solution respectively in the same manner; (4) using a spectrophotometer to measure the absorbance of the colorimetric solution and the reference solution of the gadolinium standard solution to obtain a standard curve, wherein the abscissa of the standard curve is the total content of lanthanum and cerium, and the ordinate is the absorbance; Under the same conditions, the absorbance of the color developing solution and the reference solution of the test sample solution is measured, and the total content of lanthanum and cerium in the test sample solution is obtained according to the standard curve, and the total content of lanthanum and cerium in the vanadium-titanium magnetite is calculated according to the following formula: In the formula: w is the total content of lanthanum and cerium, %; C is the total content of lanthanum and cerium in the test sample solution, μg / mL; C0 is the detection value of the blank solution, μg / mL; V is the total volume of the test sample solution, mL; m is the mass of the sample, μg.
2. The method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite according to claim 1, characterized in that: Step (1) Specific The following steps are involved: The sample and the acid solution are mixed at 200°C to 300°C to dissolve the sample, and then perchloric acid with a mass concentration of 30% to 50% is added and heated to evaporate at 210°C to 400°C until white perchloric acid smoke is emitted, and the container wall is rinsed with water, and the heating and evaporation are continued until the white perchloric acid smoke reaches the cup mouth, and after cooling, the salt is dissolved with water, and the volume is fixed to 50mL or 100mL with water, wherein the mass volume ratio of the sample, the acid solution and the perchloric acid is (0.10g to 3.0g): (5mL to 40mL): (4mL to 20mL).
3. The method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite according to claim 2, characterized in that: The acid solution includes nitric acid (1+3) and / or hydrochloric acid.
4. The method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite according to claim 2, characterized in that: Step (1) also includes: when the mass percentage of Cr in the sample is greater than 1.5%, removing chromium with hydrochloric acid, and then continuing to heat and evaporate to emit white perchloric acid smoke to the cup mouth.
5. The method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite according to claim 1, characterized in that: Step (2) specifically includes the following steps: The high-purity gadolinium oxide was first dried at 750° C. to 780° C. for 20 min and then cooled to room temperature. 0.1154 g was weighed and 40 ml of hydrochloric acid (1+1) was added to dissolve it. After cooling to room temperature, it was diluted to 1000 mL with water to obtain a gadolinium stock solution with a concentration of 100 μg / mL. The gadolinium stock solution was measured and diluted with the blank solution to prepare gadolinium standard solutions with gadolinium concentrations of 2.0 μg / mL, 10.0 μg / mL, and 100 μg / mL, respectively.
6. The method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite according to claim 1, characterized in that: In step (3), the preparation process of the color developing solution and the reference solution is as follows: Take the sample solution to be tested and add oxalic acid and chlorophosphazo mA in sequence, and dilute to volume with water to obtain a color developing solution, wherein the volume ratio of the sample solution to be tested, oxalic acid and chlorophosphazo mA is (5.00-50.00): (5-20): (5-20); Take a blank solution and add chlorophosphonazo mA to make a constant volume to obtain a reference solution, wherein the volume ratio of the blank solution to chlorophosphonazo mA is (5.00-50.00):(5-20).
7. The method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite according to claim 6, characterized in that: The concentration of the oxalic acid is 40 g / L to 250 g / L; the concentration of the chlorophosphonazo mA is 0.2 g / L to 4 g / L.
8. The method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite according to claim 1, characterized in that: Step (4) specifically includes the following steps: The sample color developing solution and the sample reference solution are placed in an absorption dish of 1 cm, 2 cm or 3 cm, and the reference solution is used as a reference. The absorbance is measured at 560 nm to 760 nm using a spectrophotometer to obtain the total content of lanthanum and cerium in the test sample solution and the detection value of the blank solution, and the total content of lanthanum and cerium in the vanadium-titanium magnetite is calculated.
9. The method for detecting the total content of lanthanum and cerium in vanadium-titanium magnetite according to claim 1, characterized in that: The total mass content of lanthanum and cerium in the sample is 0.0001% to 1.0%.
Citation Information
Patent Citations
Method for determining content of lanthanum, cerium, praseodymium, neodymium and samarium in iron-containing dust sludge
CN104483375A
Chemical analysis method of lanthanum in lead-base alloy
CN105486651A
Dissolving method for lanthanum-cerium-terbium phosphate and its analysis
JP1997067110A
Zirconium concentration analyzing method of ferro-silicon alloy by an inductively coupled plasma spectrometer for accurately and quickly analyzing density of zirconium among a sample
KR1019990051986A
Cited By
Spectrophotometric detection method for lanthanum-alizarin complexing ketone of fluorine element in tantalum-niobium material
CN120334215A
Spectrophotometric determination method of lanthanum-alizarin complex ketone of fluorine in tantalum-niobium materials
CN120334215B